Covid-19: Upaya Preventif dan Kuratif ala Ibu Hamil - Astry Ayu Praharsini (Universitas Muslim Maros, 2021)
In 2020 all countries in the world are busy with a pandemic caused by the Covid-19 Virus. Indonesia is one of the countries whose citizens have been infected with Covid-19 since March 2020 and its spread is fast. Symptoms of being infected with Covid-19 are cough, fever, shortness of breath, anosmia and muscle aches, but in some cases, a person who is exposed to Covid-19 does not even show symptoms at all. Covid-19 can attack various ages ranging from children to the elderly, gender, including pregnant women. Pregnant women are stated to be very vulnerable to contracting Covid-19 with various other diseases, the fear of fetal growth and development cannot be separated from the mother's worries during the Covid-19 pandemic. This article deals with how pregnant women prevent being infected with Covid-19 and how they treat themselves when infected with Covid-19. This research was conducted in the city of Makassar. The informants involved in this study consisted of 10 pregnant women who are varied on the basis of age (between 19 and 26 years, gestational age (between 12 and 32 weeks) and occupation (seven housewives, a celebgram, a pharmacist, and a nurse). Data was collected usingthe combination of interview and observation. In this study, it was found that the positive impacts of Covid-19 pandemic for pregnant women that their togetherness with members of the family becomes more intensive because they spend more time at home, they are more concerned about personal and family hygiene, they are more physically and mentally healthy, and they become more creative in using their free time. While the negative impact of Covid-19 for pregnant women is that they experience anxiety during the Covid-19 period. However, those who have a better understanding of Covid-19 tend to be positive in dealing with it. Although the efforts made by pregnant women in relation to prevention and treatment are similar but not the same, in preventive efforts, pregnant women are more likely to combine physical activity and various intakes related to efforts to maintain immunity. Meanwhile, in curative efforts, pregnant women limit the duration of physical activity and are more routine in carrying out healing efforts. The difference in nutritional intake also lies in vitamin supplements. In preventive efforts the consumption of supplements is not so ignored and focused on the food consumed, while in a curative effort, they tend to balance food intake and supplements to maintain immunity and accelerate recovery. It is argued in this article that despite the fact pregnant women are vulnerable group, they do not have their own specific treatment either to prevent or to treat them in relation to Covid-19.